Efektivitas Teknik Permainan Simulasi dengan Menggunakan Media Dart Board untuk Meningkatkan Motivasi Belajar Siswa Kelas VII C SMP Negeri 2 Tegal Siwalan Probolinggo - Ninda Ayu Putri Cahyani; Khairul Bariyyah; Leny Latifah (JKI (Jurnal Konseling Indonesia), 2017)
This research is based on the results of observations to students of class VII C SMP Negeri 2 Tegal Siwalan, indicating that 9 students still have low levels of learning motivation. This can hinder the development of students in achieving their goals and can lead to failure of learning. Therefore, the increase in student learning motivation is necessary for students. This study used pre-experimental designs with one group pre-test and post-test design. Subjects used in this study were 9 students from grade VII C SMP Negeri 2 Tegal Siwalan. The sampling technique was done by purposive sampling which only studied the students with low learning motivation. The research instrument used is the scale of learning motivation, anecdotal note, and treatment material that has been tested before the expert given to the subject. Data were analyzed by using Wilcoxon Signed Rank Test. Based on the result of the research shows (1) Student motivation before treatment has low motivation level (2) Student motivation after treatment has increased learning motivation into high category (3) Simulation game technique using to dart board media effectively improves students learning motivation. This means that is simulation game technique using the effective media dart board to improve the learning motivation of the students in grade VII C SMP Negeri 2 Tegal Siwalan Probolinggo.